Profile of engineering education in India status, concerns and recommendations - Biswas, Gautam; Chopra, K.L; Jha, C.S; Singh, D.V (Narosa Publishing House, 2010)
This book addresses various issues pertaining to engineering education in India. One of the mandates of the Indian National Academy of Engineering, an apex body of distinguished engineers and scientists, is to set up tracks for the countrymen for achieving excellence in engineering education. This book aims to identify such tracks. The obligations and rights of the stake holders and the government vis-à-vis engineering education are also discussed at length. The present engineering education and the skills it imparts to students are inadequate to meet new and emerging challenges of equality of capabilities which is required for international mobility in the WTO environment. Since India is not yet a member of the Engineers Mobility Forum and only a provisional member of the Washington Accord at present, recognition of our Engineering degrees abroad is not automatic. Of course, due to their generally recognized brand names, the degrees from IITs and many other prominent engineering institutions in the country are readily recognized in most countries. Steps are presently being taken by the National Board of Accreditation of AICTE to obtain full membership of the Washington Accord. Re-engineering the engineering education to achieve excellence and sustain it thus an important objective. This book represents a systematic analysis highlighting the issues related to this objective. The book is the outcome of an INAE-sponsored research study that examines the challenges faced by engineering education in terms of access, equity, regional imbalance and quality. The study is also aimed at analyzing the weaknesses of the present system and identifying the requirements of the modern teaching-learning processes. The study suggests measures for improvement in faculty qualifications and competence, and finally, it provides some insight for instituting healthy academic governance.